2019
DOI: 10.1021/acsbiomaterials.9b00773
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid-Conjugated Radioluminescent Calcium Tungstate Nanoparticles as Radio-Sensitizers for Cancer Radiotherapy

Abstract: Radiation therapy is a primary treatment modality for many forms of cancer. Normally, the highest tolerable dose of ionizing radiation is used to treat tumors, but limitations imposed by normal tissue complications present challenges for local tumor control. In light of this, a class of compounds called radio-sensitizers have been developed to enhance the effectiveness of radiation. Many of these are small molecule drugs found to interact favorably with radiation therapy, but recent advances have been made usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…It exhibited sensitizer enhancement ratios (SER) of 1.45 and 1.21 at a 10% survival fraction. Colongenic cell survival assay showed that CaWO 4 exhibited a sensitization ratio (SER) of 1.21 at a 10% survival rate [ 52 ]. In 2017, Zhao et al studied the radiosensitization effect of GdW10 on BEL-7402 cells, and the results showed that the SER was 1.28 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It exhibited sensitizer enhancement ratios (SER) of 1.45 and 1.21 at a 10% survival fraction. Colongenic cell survival assay showed that CaWO 4 exhibited a sensitization ratio (SER) of 1.21 at a 10% survival rate [ 52 ]. In 2017, Zhao et al studied the radiosensitization effect of GdW10 on BEL-7402 cells, and the results showed that the SER was 1.28 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This mixture was then vortexed for 30 s to complete the resuspension. These particles were then filtered with a 450 nm PTFE syringe filter …”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] The most promising RLNP compositions utilize lanthanide ions as activators doped into various inorganic hosts such as oxides, tungstates, aluminates, oxysuldes and uorides, among others. [5][6][7][8] Lanthanide-doped nanoparticles based on a uoride host have attracted considerable attention due to their unique properties, such as wide band gap, low phonon energy, and high chemical and radiation stability. 9,10 Thus, uoride-based lanthanide-doped nanoparticles have emerged as strong candidates for achieving efficient 4f n -4f n emissions under ionizing excitation.…”
Section: Introductionmentioning
confidence: 99%